Influence of hydrofluoric acid etching time and concentration on shear bond strength of metal brackets to ceramic surfaces - ANDRADE,Cedirlei Gomes da Silveira (2019)
Abstract Introduction Surface treatment prior to bonding ceramic brackets with hydrofluoric acid is indicated because of its ability to promote morphological changes necessary for adhesion. Objective To evaluate the shear bond strength (RUC) of metal brackets bonded to the feldspar ceramic surface under the action of hydrofluoric acid (AF), in different concentrations (5% and 10%) and different application times (30 and 60 seconds). Material and method Four nickel-chrome metal blocks that received an application of feldspathic ceramic were used, to which 80 metal brackets (Abzil/3M) were bonded and divided into 4 Groups (n=20) according to the acid etching procedure. The blocks were etched with 5% hydrofluoric acid for 30 and 60 seconds (AF5/30 and AF5/60, respectively) and 10% hydrofluoric acid for 30 and 60 seconds (AF10/30, AF10/60, respectively). The resin composite used was Transbond XT (3M) and the presence of a glazer was maintained on the ceramic surface. The specimens were placed on a Universal test machine Instron 4411 (Instron Corp, USA) to which a chisel was adapted to perform the shear test at a speed of 1mm/min. The data were submitted to the analysis of variance (ANOVA) and the Adhesive Remnant Index was evaluated. Result In the time interval of 30 seconds, there was no significant difference for the 5% and 10% hydrofluoric acid concentrations. In the 60-second time interval, the 10% concentration showed significantly higher shear bond strength values (p<0.05). The ARI showed predominance of scores 1 and 2. Conclusion It was concluded that 10% hydrofluoric acid showed higher shear bond strength values in 60 seconds of etching, while 5% hydrofluoric acid showed no significant difference between the etching times.